2002
DOI: 10.1007/bf03214831
|View full text |Cite
|
Sign up to set email alerts
|

High energy states of goldand their importance in electrocatalytic processes at surfaces and interfaces

Abstract: The ability of metals to store or trap considerable amounts of energy, and thus exist in a non-equilibrium or metastable state, is very well known in metallurgy; however, such behaviour, which is intimately connected with the defect character of metals, has been largely ignored in noble metal surface electrochemistry. Techniques for generating unusually high energy surface states for gold, and the unusual voltammetric responses of such states, are outlined. The surprisingly high (and complex) electrocatalytic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 39 publications
1
32
0
Order By: Relevance
“…[22][23][24][25]. In the course of this work it has been found that a prior cathodic treatment accelerated subsequent oxide formation during an anodic excursion, with the effect exacerbated for prolonged prior cathodisation [24]. In the present work the gold electrode was first cycled ten times between -1.5 and 0 V vs SCE to clean the surface.…”
Section: 2mentioning
confidence: 83%
See 2 more Smart Citations
“…[22][23][24][25]. In the course of this work it has been found that a prior cathodic treatment accelerated subsequent oxide formation during an anodic excursion, with the effect exacerbated for prolonged prior cathodisation [24]. In the present work the gold electrode was first cycled ten times between -1.5 and 0 V vs SCE to clean the surface.…”
Section: 2mentioning
confidence: 83%
“…23,24,25]. In broad summary the formation of gold oxide starts at about +1.1 to 1.2 V vs SCE on an annealed sample, but may start at potentials of as low as +0.2 V vs SCE on a severely cathodised sample [25].…”
Section: Electrochemistry Of Gold Ultracapacitorsmentioning
confidence: 97%
See 1 more Smart Citation
“…1. Burke et al have shown that this peak can be enhanced, as well as other processes well within the double layer region, by thermal and electrochemical activation of bulk gold electrodes [32][33][34]. This creates a disordered surface which is prone to oxidation at potentials below that for monolayer oxide formation.…”
Section: Resultsmentioning
confidence: 99%
“…Adatoms are so-called metastable, active (or low lattice coordination state) surface metal atoms, such as terrace, step, ledge and kink atoms [3][4][5][6]. It has been pointed out that some metals, e.g.…”
Section: Introductionmentioning
confidence: 99%